Importance of Mineral Fertilizers in Winter Wheat Crop Rotation - Mamurakhan , Atabaeva; Qutlug‘bek o‘gli , Haydarov Ruslan (American Journal of Biology and Natural Sciences, 2024)
The order and timing of irrigation of winter cereal crops, the number of irrigations, the irrigation rate, the climate of the region, the soil hydrogeological conditions, as well as the biological characteristics of the variety being planted and the level of agricultural technology used are determined. In crop rotation for winter wheat, it is very demanding on predecessors and soil fertility and fertilization.